Konsekuensi dari E-Service Quality pada Online Food Delivery Applications di Indonesia - Farah Zhafirah Yasmin (Peneliti.net, 2023)
This study aims to analyze and identify the role of e-service quality, perceived value, customer satisfaction, and customer loyalty on repurchase intention among consumers who use online food delivery applications. The sampling method used was purposive sampling with a sample of 200 respondents. Structural Equation Model (SEM) is a method applied in data analysis. The results of this study are 1) e-service quality has positive effect with perceived value and customer satisfaction, 2) e-service quality, perceived value, and customer satisfaction has positive effect with customer loyalty, and 3) customer loyalty has positive effect on repurchase intention.